PUBLIC SERVICE INNOVATION AT THE INVESTMENT SERVICE OFFICE AND ONE-STOP WORKFORCE SERVICE (DPMPTSPTK) BARRU REGENCY - Muliati Muliati; Wahyul AZ (Sean Institute, 2023)
This study aims to find out: Public Service Innovation in Service Offices Investment and One-Stop Workforce Services (DPMPTSPTK) Baru district. And to find out the supporting factors in public service innovation in improving the quality of service in the investment service and integrated services one door of labor in Barru Regency. Source of data obtained by observation participants, in-depth interviews, and documentary studies. Innovation is an idea, practice, or objects that are considered new by individuals one unit of other adoption. Public service is activities or a series of activities in order to fulfill the appropriate service needs with statutory regulations for every citizen and resident of goods, services, and/or administrative services provided by public service providers namely state administration institutions, cooperatives, independent institutions formed under the law for public service activities and other legal entities formed solely for public service activities.